Efektivitas Penggunaan E-LKPD Berbasis Guided Inquiry Pada Materi Pemanasan Global Terhadap Peningkatan Pemahaman Konsep Peserta Didik - Anggi Namira Siregar; Zuhdan Kun Prasetyo; Jumadi Jumadi; Diyen Paramitha (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of guided inquiry-based E-LKPD on students' global warming material. This type of research uses a pretest-posttest design. The population of this study were all students of MAN 1 Yogyakarta. The research sample was 64 divided into two classes. Data collection on concept understanding uses multiple choice tests. Research data was collected from the pre-test and post-test understanding of the concept of global warming material. The results of the research show that E-LKPD based on guided inquiry on global warming material is less effective in increasing the conceptual understanding of class obtained was 0.77 in the high category and 77% in the effective category.